Adopsi teknologi finansial dan pertumbuhan ekonomi: Studi panel lintas negara antara Singapura dan Malaysia - Hakim, Syahrul; Rahajuni, Dijan; Zakaria, Rinny (Nur Science Institute, 2024)
This study analyzes the impact of fintech adoption on economic growth in Singapore and Malaysia during 2015-2023 using quantitative methods and the Common Effect Model (CEM) panel data regression approach. The results show that fintech adoption has no significant effect on economic growth in both countries, and only 0.44% of the variation in economic growth can be explained by fintech. In comparison, other factors influence 99.56% in both countries. Based on the analysis, the adoption of fintech theoretically has a positive impact on economic transformation and growth. However, from an empirical perspective, the effect of fintech on economic growth in both countries is not statistically significant during the study period (2015-2023). This study confirms the importance of fintech interaction with other macroeconomic policies to optimize its impact on economic growth. Strategic policy support and digital investment are needed to accelerate economic transformation in Singapore and Malaysia.